(untitled) (Web of Teachers: Inderscience Research, 2024)
This article provides information about the unique features of speech therapy work with blind children. Due to the impairment of the vision analyzer, the speech development of blind and partially sighted children has its own characteristics, which is reflected in speech (echolalia, "formalism", vocabulary disorders, etc.).